Prediksi Model Zonifikasi Wilayah Peri-urban Kota Bandung Bagian Timur - Darwin, Ira Safitri; Darmaputra, Pramudya Alif (Fakultas Seni Rupa dan Desain ITB, 2025)
Urbanization pressure has driven the expansion of Bandung's urban area to the East, especially in Cileunyi, Rancaekek, and Jatinangor Districts. As a peri-urban area of Bandung City, which is a transition zone between urban and rural areas, the challenges of its development are increasingly complex, especially since the area has physical limitations but does not hinder land conversion. This study aims to predict land cover changes and zonification models in the Eastern peri-urban area of Bandung City using the Cellular Automata Markov model. The results indicated that urban growth in the peri-urban area of Bandung City, especially in Cileunyi District, occurred significantly, forming an urban-rural frame zone (zobikodes). This pattern indicates strong competition between development interests and environmental conservationefforts. This transformation indicates that urbanization in the peri-urban area is not only triggered by population growth but also by economic dynamics, accessibility, and spatial planning policies that have not been fully able to control urban sprawl. The conclusion of this study confirms that without stricter and evidence-based policy interventions, uncontrolled urban expansion risks accelerating environmental degradation, reducing ecological resilience, and threatening the sustainability of agricultural land. Therefore, the resulting zonification models can be the basis for formulating a more adaptive and sustainable spatial planning strategy to balance economic growth with environmental preservation in the peri-urban areas of Eastern Bandung City.